Penelitian bertujuan untuk menganalisis pengaruh kompensasi manajemen dan kualitas audit terhadap tax avoidance serta menguji peran board gender diversity sebagai variabel moderasi. Objek penelitian ini berupa perusahaan sektor pertambangan yang terdaftar - Hannisa Yuiandini; Masripah - (JURNAL PAJAK INDONESIA, 2023)
This research was conducted to analyze the effect of management compensation and audit quality on tax avoidance and to test the board gender diversity's role as a moderating variable. The object of this research is a mining sector company listed on the Indonesia Stock Exchange (IDX) in 2019-2021, with a total sample of 25 companies. This study uses quantitative methods with panel data. Data analysis techniques used were descriptive statistical tests, normality tests, regression model selection tests, classical assumption tests, and hypothesis testing with a significance level of 10%. The results show that management compensation has no significant effect on tax avoidance, audit quality has a significant negative effect on tax avoidance, board gender diversity cannot moderate the relationship between management compensation and tax avoidance, board gender diversity cannot moderate the relationship between audit quality and tax avoidance. The implications of this research include, (1) companies can present specialized audit partners in order to prevent management actions that change the fairness of presenting financial statements through tax avoidance. (2) for investors, the results of this study become a consideration in choosing investments with good prospects for business success, not because the company has taken advantage of a tax loophole.